2016
DOI: 10.1021/acs.jpcc.6b09460
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Composition and Kinetics of the in Situ Replacement in CH4–CO2 Hydrate System

Abstract: The exchange process between CO2 and methane hydrate has been observed in numerous laboratory experiments, computer simulations, and recently confirmed in a field test. Yet, to date there is no kinetic model capable of accurately predicting the swapping process at given fluid composition and p-T conditions. Major obstacles on the way to an adequate mathematical description are caused by the insufficient characterization of experimental environments and a nearly complete lack of information on the time-resolved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
86
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(86 citation statements)
references
References 77 publications
(226 reference statements)
0
86
0
Order By: Relevance
“…In the second phase the pressure in the cell is slowly increasing again, complemented by a parallel further, gentle CH4 increase in the vapor phase, indicating that a coupled gas exchange of CH4 by CO2 in the hydrate phase becomes the dominant process. This direct gas hydrate conversion has been described previously by the shrinking-core process [57]. Visual observation of the evolution of the different phases during gas hydrate crystallization (from left to right: directly after water injection; after stirrer has been set to 400 rpm; 1 min after the gas hydrate formation incipient; 48 min after the gas hydrate formation incipient).…”
Section: Ch 4 -Co 2 Exchange Between a Vapor Phase And A Bulk Gas Hydmentioning
confidence: 57%
See 1 more Smart Citation
“…In the second phase the pressure in the cell is slowly increasing again, complemented by a parallel further, gentle CH4 increase in the vapor phase, indicating that a coupled gas exchange of CH4 by CO2 in the hydrate phase becomes the dominant process. This direct gas hydrate conversion has been described previously by the shrinking-core process [57]. Visual observation of the evolution of the different phases during gas hydrate crystallization (from left to right: directly after water injection; after stirrer has been set to 400 rpm; 1 min after the gas hydrate formation incipient; 48 min after the gas hydrate formation incipient).…”
Section: Ch 4 -Co 2 Exchange Between a Vapor Phase And A Bulk Gas Hydmentioning
confidence: 57%
“…In the second phase the pressure in the cell is slowly increasing again, complemented by a parallel further, gentle CH 4 increase in the vapor phase, indicating that a coupled gas exchange of CH 4 by CO 2 in the hydrate phase becomes the dominant process. This direct gas hydrate conversion has been described previously by the shrinking-core process [57].…”
Section: Ch 4 -Co 2 Exchange Between a Vapor Phase And A Bulk Gas Hydmentioning
confidence: 79%
“…According to literature, the interactions between a CO 2 phase and an initial CH 4 hydrate phase are described as a replacement of the encased CH 4 molecules with CO 2 molecules: The process is divided into two steps. The first step is a fast reaction at the interface between the hydrate grain and the CO 2 fluid, where a partial destruction of the hydrate cavities and/or rearrangements of water molecules results in a fast release of CH 4 molecules (Falenty et al, ; Ota et al, ). According to Falenty et al (), this destruction is limited to the surface before new, mixed hydrate forms.…”
Section: Resultsmentioning
confidence: 99%
“…Depending on the experimental conditions, the amount of CH 4 recovered from a hydrate phase due to CO 2 replacement varied from 15% in 800 hr (Hirohama et al, ) to 50% within 5 hr (Lee et al, ) to 60% in 300 hr (Kvamme et al, ), to give just few examples. It could be shown that the exchange of CH 4 with CO 2 initially takes place at the surface of the hydrate grain and goes along with a partial opening or rearrangement of the cavities (Falenty et al, ; Ota et al, ; Schicks et al, ). Laboratory experiments usually avoid free pore water that may transform into CO 2 hydrate when CO 2 is injected resulting in a decrease of permeability and thus reduced injectivity or clogging.…”
Section: Introductionmentioning
confidence: 99%
“…The Ignik Sukumi trial in 2012 (e.g., Boswell et al, ) involved such an apparent exchange of CO 2 for methane within the gas hydrates in a permafrost‐associated reservoir near Prudhoe Bay, Alaska. Both CO 2 and CH 4 form Structure I gas hydrates, and some studies have suggested that replacement of methane by CO 2 in the reservoir's gas hydrates may occur without dissociation of the original methane hydrate (Falenty et al, ; Ota et al, ). The results of Schicks et al () indicate that methane hydrate underwent conventional depressurization‐driven dissociation during injection of CO 2 and N 2 in the Ignik Sikumi test and imply that a mixed hydrate containing all three gases may have formed in the reservoir.…”
Section: Special Section Themesmentioning
confidence: 99%